Bilateral foreign aid: how important is aid effectiveness to people for choosing countries to support?. Issue 5 (12th March 2017) - Cunningham, Harry; Knowles, Stephen; Hansen, Paul
ABSTRACT: We conduct a discrete choice experiment to determine how important aid effectiveness is to people relative to other criteria for choosing countries to support with bilateral foreign aid. We find that aid effectiveness is important, on a par with recipient-country need as proxied by the level of hunger and malnutrition. Both criteria are more important than others.